KAJIAN KADAR HCN DAN KARAKTERISTIK PATI PADA TEPUNG KORO PEDANG (Canavalia ensiformis) BERDASARKAN WAKTU PERENDAMAN BIJI DALAM AIR PANAS DAN LARUTAN NATRIUM BIKARBONAT (NAHCO3) - Putro, Novita Tommy Lasmono; Arisasmita, Joek Hendrasari; Srianta, Ignatius (Jurnal Teknologi Pangan dan Gizi, 2015)
Jack bean (Canavalia ensiformis) is potential utilized as food ingredient because it contains high nutrients, but it contains high glucocyanide (toxin) and has hard texture. This problem can be overcome by the aim of soaking to soften the texture and reduce the toxins to produce an edible and safety flour. The research aim is to examine the influence of media types and soaking time (12, 18, 24 hours) on HCN content and starch characteristics in jack bean flour. The research design was nested randomized block using two factors (media types and soaking time). The treatments are soaking in water (95±2°C) and sodium bicarbonate solution 0,4%, for 12 ,18 ,24 hours. Dependent variables measured in this study were levels of HCN, starch content, resistant starch content, starch granule profile, and viscoamylography. The data obtained were analyzed using ANOVA at α = 5% for determining whether or not significant differences between treatments in the study. Data rocessing followed by LSD test (Least Significant Different) at α = 5% if there is a significant effect by treatment. The results showed that the characteristics of starch and HCN levels were affected by the treatment significantly. Total starch content and gelatinization temperature from soaking in hot water were 51,30%; 86°C while sodium bicarbonate were 44,29%; 86,38°C. Resistant starch contents were between 11.90% to 18.52%. HCN content from soaking during 24 hours were resulting the minimum level, where soaking in hot water and sodium bicarbonate were 9,4997 mg/kg and 10,8279mg/kg respectively.